‘Trendy Party-Goers.’ Ordinary Forms of Recreation and the Media in African Urban Margins - (:unkn) unknown (My University, 2018)
Based on an ethnography conducted in the urban margins of Dakar (Senegal) and Nairobi (Kenya), the article shows how the ritualization of social life is amplified in these contexts where certain forms of technological hypermodernity are intertwined with the bricolage of precariousness. Complementary to, and yet distinct from, the big celebration that marks important family and community events, ritual festivities enliven everyday life in the neighbourhoods. Diverse and varied, carried by a subtle mix of ceremonial and pragmatism, these smaller festive sociabilities draw on traditionnal ritual frameworks, urban contexts and current media cultures. Maintaining the good atmosphere and vibrations, or enjaillement according to the popular urban slang, thus becoming a practice that supports anti-past parts of lived experience—including daily labour and social relationships—by integrating them more into the registers of entertainment. Moreover, we find an ambivalence related to that of technological mediation: on the one hand, these rituals responds to the inhabitants need for collective communion and, on the other, it materializes the desire to have fun and to escape elsewhere according to a “logic of affinity”.
Keywords: African Research